(untitled) (International Journal of Physiotherapy, 2017)
Background: Movement disorders and non-motor problems such as cognitive decline, anxiety, depression and behavioural problems, are common in people with dementia and can progress over time. Exercise coupled with music is a promising form of therapy designed to improve both the motor and non-motor manifestations of this debilitating neurological condition. Objectives: To present a protocol for a systematic review and critical analysis of the literature to answer the following questions: (i) Is music-cued exercise more effective than usual care for the treatment of motor and non-motor symptoms of dementia? (ii) What are the outcomes of music-cued exercise for people living with dementia? Methods: We provide the protocol for a systematic review and critical analysis of the literature using the PRISMA guidelines. Studies shall be reviewed that use music cued exercises aimed at improving the management of physical and non-physical problems associated with dementia. Eligibility criteria will be applied to the title and abstract of each citation as a first step followed by full text screening. Data extraction and quality appraisal are to be performed by two reviewers. Data sources: This protocol documents the comprehensive search strategy to be performed using MEDLINE, CINAHL, EMBASE, PSYCHINFO, PUBMED, SCOPUS and web of science databases. Science, technology and engineering databases will also be searched. Eligibility criteria: All study designs incorporating data will be included in this review. The following selection criteria shall be applied: • Participants will be people diagnosed with dementia, including Alzheimer’s disease, of any stage and severity, all ages, any range of co-morbidities, any medications. • Interventions will use rhythmic music with any physical exercise or rehabilitation program. • Outcomes shall include motor impairments such as gait, postural stability and general mobility. Studies considering non-motor signs such as anxiety, depression, behavioural disturbances and cognitive decline will also be included. Results: Evidence will be built from this review regarding the effectiveness of using music-cued exercises to optimise physical abilities and improve non-motor disorders in people with dementia. Conclusions: This protocol paper documents the methods that we shall use for a forthcoming systematic review. The knowledge obtained from the review will provide guidance to people with dementia, caregivers and clinicians by clarifying the strength of the evidence for music-cued movement rehabilitation.